Secrets - Michaels, Fern (New York, NY : Kensington Publishing Corp., 2022)
When they find themselves saddled with life or death information, two siblings, and owners of an antique shop/café, realize they have no one to turn to but each other.
Keywords: Siblings -- Fiction; Families -- Fiction; Antiques business -- Fiction; Furniture -- Repairing -- Fiction; Diaries -- Fiction; Antiques business; Siblings; Diaries; Families; Furniture -- Repairing; North Carolina -- Fiction; North Carolina; Fiction; Novels; Romance fiction; Thrillers (Fiction); Thrillers (Fiction); Romance fiction; Novels